Hubungan Antara Indeks Massa Tubuh (IMT) Dengan Kejadian Dismenore Primer Pada Mahasiswi Semester 7 Fakultas Kedokteran Universitas Hang Tuah Surabaya - A. A. Sagung Amanda Achintya (Universitas Hang Tuah, 2017)
Background: The incidence of dysmenorrhea, or painful when menstruation, is very high. There are many risk factors of dysmenorrhea, one of them is Body Mass Index (BMI). Women with low BMI (underweight) tend to experience dysmenorrhea, while women with high BMI (overweight – obese) also tend to experience it. This research aimed to determine the correlation between Body Mass Index (BMI) and primary dysmenorrhea in the 4th year medical students at the Faculty of Medicine Hang Tuah University. Objective: The aim of this study is to determine anatomical variation of the mental foramen in mandible of human skull. Anatomical variation in this study is the position, number, and size of the mental foramen. Methods: This research was an observational analytic study with cross sectional design, conducted in January 2017. This research used weight and height measurement of BMI. BMI was classified into 2 groups: normal BMI and abnormal BMI (Underweight and Overweight-Obese). A questionaire was used to obtain data of dysmenorrhea. Total respondent of this research was 55 students that met the inclusion criteria, but did not meet the exclution criteria. Result: The results of this research showed from a total of 55 respondents, 40 respondents (72,7%) had experienced dysmenorrhea, while 15 respondents (27,3%) had never experienced dysmenorrhea. Among 40 respondents that had experienced dysmenorrhea, 14 respondents (35%) had an abnormal BMI, while 26 respondents (65%) had a normal BMI. In addition, among 15 respondents that had never experienced dysmenorrhea, only 1 respondent (6,7%) had an abnormal BMI while 14 respondents (93,3%) had a normal BMI. Conclusion: The result of relative risk (RR) calculation showed respondents with an abnormal BMI had 1,436 fold higher risk of experiencing dysmenorrhea compared to respondents with a normal BMI. The result of Spearman analysis showed p =0,036, or p<0,050. Therefore, we concluded there was a significant correlation between BMI and primary dysmenorrhea in the 4th year medical students at the Faculty of Medicine Hang Tuah University.